Correlating Electronic Structure and Device Physics with Mixing Region Morphology in High‐Efficiency Organic Solar Cells. Issue 6 (12th January 2022) - Leng, Shifeng; Hao, Tianyu; Zhou, Guanqing; Zhu, Lei; Zhong, Wenkai; Yang, Yankang; Zhang, Ming; Xu, Jinqiu; Zhan, Junzhe; Zhou, Zichun; Chen, Jiajun; Lu, Shirong; et al.
Abstract: The donor/acceptor interaction in non‐fullerene organic photovoltaics leads to the mixing domain that dictates the morphology and electronic structure of the blended thin film. Initiative effort is paid to understand how these domain properties affect the device performances on high‐efficiency PM6:Y6 blends. Different fullerenes acceptors are used to manipulate the feature of mixing domain. It is seen that a tight packing in the mixing region is critical, which could effectively enhance the hole transfer and lead to the enlarged and narrow electron density of state (DOS). As a result, short‐circuit current ( J SC ) and fill factor (FF) are improved. The distribution of DOS and energy levels strongly influences open‐circuit voltage ( V OC ). The raised filling state of electron Fermi level is seen to be key in determining device V OC . Energy disorder is found to be a key factor to energy loss, which is highly correlated with the intermolecular distance in the mixing region. A 17.53% efficiency is obtained for optimized ternary devices, which is the highest value for similar systems. The current results indicate that a delicate optimization of the mixing domain property is an effective route to improve the V OC, J SC, and FF simultaneously, which provides new guidelines for morphology control toward high‐performance organic solar cells. Abstract : A tight packing in the mixing region effectively enhances the hole transfer and leads to the enlarged and narrow electron density of state. The optimized electronic structure effectively increases carrier density and reduces the recombination losses due to the reduced energy disorder, improving the open‐circuit voltage, short‐circuit current and fill factor simultaneously.